2008
DOI: 10.1002/hep.22342
|View full text |Cite
|
Sign up to set email alerts
|

Orphan receptor small heterodimer partner suppresses tumorigenesis by modulating cyclin D1 expression and cellular proliferation†

Abstract: The small heterodimer partner (SHP; NROB2), a member of the nuclear receptor superfamily, contributes to the biological regulation of several major functions of the liver. However, the role of SHP in cellular proliferation and tumorigenesis has not been investigated before. Here we report that SHP negatively regulates tumorigenesis both in vivo and in vitro. SHP−/− mice aged 12 to 15 months old developed spontaneous hepatocellular carcinoma, which was found to be strongly associated with enhanced hepatocyte pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
127
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(132 citation statements)
references
References 24 publications
4
127
1
Order By: Relevance
“…For example, SHP, a typical target gene of FXR, has been shown to suppress cell proliferation and promote apoptosis (23). It is reported that the expression of SHP was downregulated in human HCC, and mice with SHP deficiency developed spontaneous liver tumors (24,26). The accumulating data suggest that FXR may be a pharmaceutical target for the treatment of the associated cancers including HCC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, SHP, a typical target gene of FXR, has been shown to suppress cell proliferation and promote apoptosis (23). It is reported that the expression of SHP was downregulated in human HCC, and mice with SHP deficiency developed spontaneous liver tumors (24,26). The accumulating data suggest that FXR may be a pharmaceutical target for the treatment of the associated cancers including HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, chronic deregulation of SHP expression may lead to pathologic consequences and favor liver disease. The potential negative consequences of SHP deregulation can be extrapolated from studies with liver-specific SHP-transgenic and SHP-deficient mice (Wang et al, 2003;Boulias et al, 2005;Park et al, 2008;Zhang et al, 2008Zhang et al, , 2010Zhang et al, , 2014Chanda et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…SHP KO mice are known to have various phenotypes, such as mild defects in bile acid homeostasis, 18 repression of osteoblast differentiation and decreases in bone mass, 36 enhancement of hepatocyte proliferation and transformation, 37 and susceptibility to endotoxin-induced sepsis. 17 However, no clear cardiac phenotypes have been reported.…”
Section: Discussionmentioning
confidence: 99%